Study of p53 and EGFR oncoprotein expression in oropharyngeal squamous cell carcinomas with positive and negative p16 status - Rakhmanov , V.V.; Shponka , I.S. (Морфологія / Morphologia / Morfologìâ, 2022)
Background. Squamous cell carcinoma is the most common variant of oropharyngeal cancer, including such sites as the root of the tongue, tonsils, and adenoids. One of the main changes in the WHO classification of head and neck tumors in 2017 is the recognition of the oropharynx as an independent subsite, due to the significant distribution of high oncogenic risk human papillomavirus-related squamous cell carcinomas in this location. The risk group consists of white men over 40 years of age with a high social status, and the incidence of oropharyngeal squamous cell cancer increases with age. The aim of the study was to compare the expression levels of p53 and EGFR markers in HPV-positive (p16+) and HPV-negative (p16-) squamous cell carcinomas of the oropharynx (oropharyngeal carcinomas). Methods. In the work, the biopsy and surgical material of squamous cell carcinomas of 50 patients (16 women and 34 men) who were treated at the Dnipropetrovsk Regional Clinical Hospital named after I.I. Mechnikova Hospital of Dnipro in the period from 2019 to 2021. The age of the patients ranged from 41 to 80 years; the average age was 58.56±9.75 years. Primary monoclonal antibodies to p16 (RTU), p53 (RTU), EGFR (RTU) and the UltraVision Quanto imaging system (LabVision) were used for immunohistochemical examination. Results and conclusion. The positive status of oncoprotein p16 / HPV (+) showed a statistically significant increase in occurrence in samples of squamous cell carcinomas of the oropharynx among women (p<0.05) and in the age group of patients 50-59 years old (p<0.05); in addition, all p16 / HPV (+) oropharyngeal squamous cell carcinoma samples had p53 expression below the 25% threshold. The analysis of p53 oncoprotein expression revealed a reverse trend to p16, the largest number of cases of oropharyngeal squamous cell carcinomas with p53≥25% were found among men (p<0.05) and in the age group of patients 60-69 years old (p<0.05). The highest number of cases of EGFR expression with a high score (2+,3+) was noted among men (p<0.05) and in oropharyngeal squamous cell carcinomas with p53≥25% expression (p<0.05).